Experimental study on the behaviour of shrinkage and compaction between peat and modified peat soil - Gaddafi, Ismaili (Universiti Malaysia Sarawak, UNIMAS, 2005)
Peat has a unique properties from other soil due to its organic content, which is more that 75%. Beside that, peat is also known as a problematic soil especially in engineering field for development sector as well as agricultural sector.